The Role of The KAKAK Surakarta Foundation as A Companion for Child Grooming Victims through Social Media - Oudya Nisa Tallya Handono; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2026)
The development of social media has expanded the space for children to interact, but at the same time opened up opportunities for child grooming as a form of manipulative approach that leads to sexual exploitation. This condition places children in a vulnerable position due to their inability to recognize external dangers and demonstrates that case handling does not stop at taking action against the perpetrator, but must be accompanied by assistance oriented towards the protection and recovery of the victim. This study uses an empirical legal method with a descriptive nature. Primary data was obtained through interviews with child advocates, administrators of the KAKAK Surakarta Foundation, and related parties, while secondary data was obtained through a literature review of relevant laws, books, and journals. Data were analyzed qualitatively. The novelty of this study lies in its empirical approach that focuses on the practice of victim assistance. Child grooming at the KAKAK Surakarta Foundation, thus examining not only normative aspects but also the dynamics of direct victim handling. The KAKAK Surakarta Foundation plays a role as a companion by providing child rescue, psychosocial support, legal process oversight, and strengthening children's relationships with their families and communities. The main obstacles faced include the victims' psychological condition, weak family support, the vulnerability of digital evidence, the complexity of the legal process, and social stigma. Therefore, it can be concluded that the role of companions in cases of child victimschild grooming must be understood as the implementation of legal protection so that children as victims get their rights because handling is not only measured by the punishment of the perpetrator, but also by the ability of the support system to restore children safely, fairly and with dignity.